Addressing Cognitive Impairment After Breast Cancer: What Do Women Want?. Issue 2 (March 2017) - Crouch, Adele; Von Ah, Diane; Storey, Susan
Abstract : Purpose: Cognitive symptoms in breast cancer survivors (BCSs) are common and have a disruptive impact on daily life. Breast cancer survivors frequently engage in self-management strategies to lessen the impact of these cognitive symptoms. There is little information from the perspective of BCS as to their preference of interventions. The purpose of this study was to explore how BCSs cope and self-manage the symptoms associated with cognitive changes, their preferences for the type of intervention(s), and perceived facilitators and barriers to interventions. Methods: A qualitative descriptive study using content analysis was conducted. Semistructured telephone interviews were conducted with 13 BCSs. Results: Breast cancer survivors articulated that validation and self-management strategies were used to relieve cognitive symptoms. Nonpharmacologic, evidence-based interventions that use a combined onlinein-person approach and include follow-up with healthcare providers are preferred by BCSs. Ease of use, accessibility, and convenience were identified by BCSs as most important to facilitate participation. Cost, time intensiveness, and distance to travel hampered participation. Conclusions: Patient-centered interventions tailored to meet the needs of BCSs should be considered when implementing programs or interventions to maximize their utilization and benefit. The process of implementation should be dynamic and include an ongoing collaboration between BCSs and clinical nurse specialists.